Solid supercapacitor fiber electrode and preparation method thereof

By performing high-temperature activation calcination and electrochemical deposition of MnO2 on graphene oxide fibers, MnO2@aRGOF fiber electrodes with high energy storage performance were prepared, solving the problem of low energy density of solid-state supercapacitors.

CN119581233AActive Publication Date: 2025-03-07WUHAN TEXTILE UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411516181.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-29
Publication Date
2025-03-07
Estimated Expiration
2044-10-29

AI Technical Summary

Technical Problem

Currently, solid-state supercapacitor energy density is low, and it is necessary to increase the specific capacity of supercapacitor electrode material to solve this problem.

Method used

The metal hydroxide was sprayed onto a graphene oxide film, rolled into fibers and calcined at high temperature to obtain the graphene porous fibers, and then deposited MnO2 on its surface by electrochemical deposition to prepare the MnO2@aRGOF fiber electrode.

Benefits of technology

This method simplifies process steps, reduces costs, improves the energy storage performance of the material, and the fiber electrodes exhibit excellent electrochemical properties and cycle stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119581233A_ABST
    Figure CN119581233A_ABST
Patent Text Reader

Abstract

The invention provides a solid-state supercapacitor fiber electrode and a preparation method thereof, and belongs to the field of supercapacitors. The preparation method comprises the following steps: spraying a metal hydroxide solution on a graphene oxide film, then rolling the film into fibers, then performing high-temperature activation and calcination to obtain graphene porous fibers, and then electrochemically depositing MnO2 on the graphene porous fibers to obtain the supercapacitor fiber electrode MnO2 (at) aRGOF. The preparation process conditions are simple, the porous graphene fibers are obtained through high-temperature activation and calcination, ion transmission and storage are facilitated, the MnO2 (at) aRGOF electrode is obtained through subsequent electrochemical deposition, the energy storage performance of the material is further improved, and the preparation method is suitable for industrial production. The composite electrode material as a supercapacitor fiber electrode has the advantages of excellent performance and good cycling stability, and has a wide application prospect in the field of energy storage.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of supercapacitors, and in particular to a solid-state supercapacitor fiber electrode and a preparation method thereof. Background Art

[0002] As an efficient and environmentally friendly energy storage device, supercapacitors have attracted much attention due to their fast charging and discharging and cycle stability. At present, electronic products are becoming increasingly lightweight and flexible, and the emergence of fiber-based solid-state supercapacitors is unstoppable. Solid-state supercapacitors have the advantages of high power density, stable cycle life, and fast charging and discharging, making them a very promising energy storage device. However, the current energy density of solid-state supercapacitors is still very low. In order to solve this problem, it is urgent to improve the specific capacity of supercapacitor electrode materials.

[0003] The patent with publication number CN 105810456 A discloses an activated graphene / needle-shaped nickel hydroxide nanocomposite material and a preparation method thereof. The scheme uses graphene prepared by a redox method as a raw material, KOH or NaOH as an activator, to prepare activated graphene, and loads nano-needle-shaped nickel hydroxide on the surface of the activated graphene to prepare an activated graphene / needle-shaped nickel hydroxide nanocomposite material. However, the preparation method is complicated in process, uses graphene as a raw material, and is costly.

[0004] In view of this, it is necessary to design a solid-state supercapacitor fiber electrode and a preparation method thereof to solve the above problems. Summary of the invention

[0005] In view of the technical problems existing in the background technology, the present application provides a solid supercapacitor fiber electrode and a preparation method thereof, wherein the preparation method comprises spraying a metal hydroxide on a graphene oxide film, rolling it into a fiber, and then activating and calcining it at a high temperature to obtain a graphene porous fiber (Activated RGOF or aRGOF), and then electrochemically depositing MnO on the graphene porous fiber. 2 , a solid supercapacitor fiber electrode MnO 2 The preparation process of the present invention is simple, and the porous graphene fiber is obtained by high-temperature activation calcination, which is conducive to the transmission and storage of ions, and the subsequent electrochemical deposition obtains MnO 2 @aRGOF electrode further improves the energy storage performance of the material. This composite electrode material shows the advantages of superior performance and good cycle stability as a supercapacitor fiber electrode, and has broad application prospects in the field of energy storage.

[0006] The present invention realizes reduction and activation simultaneously by calcining the precursor (mixed fibers of graphene oxide and metal oxide) at high temperature, thus simplifying the synthesis steps. Moreover, compared with graphene as a raw material, the cost of redox graphene is greatly reduced.

[0007] In a first aspect, the present invention provides a method for preparing a solid-state supercapacitor fiber electrode, comprising the following steps:

[0008] S1, spreading a graphene oxide aqueous solution with a concentration of 1 to 40 mg / ml in a mold, and placing it in a fume hood to obtain a dry graphene oxide film;

[0009] S2, preparing a metal hydroxide solution, and repeatedly spraying the metal hydroxide solution on the dried graphene oxide film obtained in step S1; then, twisting the graphene oxide film containing the metal hydroxide, rolling it into a fiber, and drying it for standby use; wherein the mass ratio of the graphene oxide to the metal hydroxide is 1:(6-16);

[0010] S3, subjecting the dried sample obtained in step S2 to high-temperature activation calcination in an argon atmosphere in a tube furnace, then ultrasonically washing it with deionized water, and finally drying it to obtain a graphene porous fiber;

[0011] S4, prepare a mixed solution of sodium sulfite and manganese sulfate, and use a three-electrode structure to conduct MnO 2 Electrochemical deposition: the working electrode is the graphene porous fiber obtained in step S3, the counter electrode is a Pt electrode, the reference electrode is a calomel electrode, and the prepared mixed solution of sodium sulfite and manganese sulfate is used as the electrolyte to perform constant current deposition; after the deposition is completed, it is thoroughly washed with deionized water and then dried to obtain a solid supercapacitor fiber electrode.

[0012] In the technical solution of the embodiment of the present application, metal hydroxide is introduced when preparing the fiber, and the metal hydroxide is activated and calcined at high temperature to activate and form pores in the graphene oxide layer to obtain porous graphene fiber (Activated RGOF or aRGOF), which is beneficial to the transmission and storage of ions, and then MnO is electrochemically deposited on the Active RGOF. 2 , providing pseudocapacitance, further increasing the energy storage performance of the fiber electrode. Actived RGOF at 0.4 mA cm -2 At a current density of , the area specific capacity can be 414.53mF·cm -2 ,Activated RGOF electrochemical deposition of MnO 2 After (MnO 2 @aRGOF), within the operating voltage range of 0 to 1.2V, it can provide 516.13mF·cm -2Area specific capacity (0.08A·cm -3 At a current density of , the volumetric capacity is 60.49F·cm -3 ).

[0013] Preferably, in step S4, during the constant current deposition process, the deposition current is 200 to 800 μA·cm -2 , the deposition time is 5 to 30 minutes.

[0014] In the technical solution of the embodiment of the present application, MnO is deposited on aRGOF by constant current. 2 , the deposition time is 5-40min, which increases the pseudocapacitance and improves the electrochemical performance.

[0015] Preferably, in step S3, the temperature control method of the high temperature activation calcination is: increase the temperature to 200-400°C at 2-20°C / min, keep warm for 10-120min, then increase the temperature to 300-1000°C at 2-20°C / min and stay for 10-120min. More preferably, the temperature control method of the high temperature activation calcination is: increase the temperature to 280°C at 2° / min, stay for 30min, then increase the temperature to 650° at 5° / min and stay for 30min.

[0016] Preferably, the heating rate in the second stage is greater than the heating rate in the first stage.

[0017] In the technical solution of the embodiment of the present application, the prepared graphene porous fiber has a three-dimensional porous structure distribution (mesopores for convenient ion transmission and micropores to further increase the energy storage performance of the material) while maintaining the integrity of the fiber.

[0018] Preferably, in step S2, the metal hydroxide solution comprises metal hydroxide: deionized water = (1-20 g): (50-500 mL).

[0019] Preferably, the metal hydroxide solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0020] Preferably, in step S4, the concentration of the sodium sulfite is 0.5-5 mol / L; the mass ratio of the sodium sulfite to manganese sulfate is (5-50):1.

[0021] Preferably, in step S2, during the drying process, the drying temperature ranges from 20 to 200° C. and the drying time ranges from 12 to 48 hours.

[0022] Preferably, in step S1, the material of the mold is polytetrafluoroethylene and the standing time is 12 to 36 hours.

[0023] In a second aspect, the present invention provides a solid-state supercapacitor fiber electrode, which is prepared by the aforementioned technical solution, and the solid-state supercapacitor fiber electrode comprises a graphene porous fiber and MnO uniformly loaded on the surface of the graphene porous fiber. 2 The solid-state supercapacitor fiber electrode can provide 516.13mF·cm in the operating voltage range of 0 to 1.2V. -2 Area specific capacity (0.08A·cm -3 At a current density of , the volumetric capacity is 60.49F·cm -3 ).

[0024] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the technical solution of the present application, the following is a brief introduction to the drawings used in the present application. Obviously, the drawings described below are only some embodiments of the present application, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.

[0026] Figure 1 This is a scanning electron microscope image of the solid-state supercapacitor fiber electrode prepared in Example 1 of the present invention.

[0027] Figure 2 This is a CV curve diagram of the solid-state supercapacitor fiber electrode prepared in Example 1 of the present invention at a voltage sweep rate of 10mv / s to 500mv / s.

[0028] Figure 3 The constant current charge and discharge test results of the solid-state supercapacitor fiber electrode prepared in Example 1 of the present invention.

[0029] Figure 4 This is the AC impedance test result of the solid-state supercapacitor fiber electrode prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0030] The following embodiments of the technical solution of the present application are described in detail in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present application, and are therefore only used as examples, and cannot be used to limit the scope of protection of the present application.

[0031] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as commonly understood by technicians in the technical field to which this application belongs; the terms used herein are only for the purpose of describing specific embodiments and are not intended to limit this application; the terms "including" and "having" in the specification and claims of this application and the above-mentioned figure descriptions and any variations thereof are intended to cover non-exclusive inclusions.

[0032] In the description of the embodiments of the present application, the technical terms "first", "second", etc. are only used to distinguish different objects, and cannot be understood as indicating or implying relative importance or implicitly indicating the number, specific order or primary and secondary relationship of the indicated technical features. In the description of the embodiments of the present application, the meaning of "multiple" is more than two, unless otherwise clearly and specifically defined.

[0033] Reference to "embodiments" herein means that a particular feature, structure, or characteristic described in conjunction with the embodiments may be included in at least one embodiment of the present application. The appearance of the phrase in various locations in the specification does not necessarily refer to the same embodiment, nor is it an independent or alternative embodiment that is mutually exclusive with other embodiments. It is explicitly and implicitly understood by those skilled in the art that the embodiments described herein may be combined with other embodiments.

[0034] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.

[0035] In the description of the embodiments of the present application, the term "multiple" refers to more than two (including two). Similarly, "multiple groups" refers to more than two groups (including two groups), and "multiple pieces" refers to more than two pieces (including two pieces).

[0036] In the description of the embodiments of the present application, unless otherwise clearly specified and limited, technical terms such as "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, it can be a fixed connection, a detachable connection, or an integral connection; it can be a mechanical connection or an electrical connection; it can be a direct connection or an indirect connection through an intermediate medium, and it can be the internal connection of two elements or the interaction relationship between two elements. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments of the present application can be understood according to the specific circumstances.

[0037] In a first aspect, the present invention provides a method for preparing a solid-state supercapacitor fiber electrode, comprising the following steps:

[0038] S1, spreading a graphene oxide aqueous solution with a concentration of 1 to 40 mg / ml in a mold, and placing it in a fume hood to obtain a dry graphene oxide film;

[0039] The mold is made of polytetrafluoroethylene and the standing time is 12 to 36 hours.

[0040] S2, preparing a metal hydroxide solution, and repeatedly spraying the metal hydroxide solution on the dried graphene oxide film obtained in step S1; then, twisting the graphene oxide film containing the metal hydroxide, rolling it into a fiber, and drying it for standby use; wherein the mass ratio of graphene oxide to metal hydroxide is 1:(6-16);

[0041] Wherein, in the metal hydroxide solution, metal hydroxide: deionized water = (1-20 g): (50-500 mL). The metal hydroxide solution is a sodium hydroxide solution or a potassium hydroxide solution.

[0042] During the drying process, the drying temperature ranges from 20 to 200°C and the time ranges from 12 to 48 hours. Preferably, the drying temperature ranges from 60 to 80°C.

[0043] S3, subjecting the dried sample obtained in step S2 to high-temperature activation calcination in an argon atmosphere in a tube furnace, then ultrasonically washing it with deionized water, and finally drying it to obtain a graphene porous fiber;

[0044] Specifically, the temperature control method of high-temperature activation calcination is a two-stage control: increase the temperature to 200-400°C at 2-20°C / min, keep warm for 10-120min, and then increase the temperature to 300-1000°C at 2-20°C / min and stay for 10-120min.

[0045] Preferably, the heating rate in the second stage is greater than that in the first stage; specifically, the temperature control method of high-temperature activation calcination is: increase to 280°C at 2° / min, stay for 30 minutes, and then increase to 650° at 5° / min and stay for 30 minutes.

[0046] S4, prepare a mixed solution of sodium sulfite and manganese sulfate, and use a three-electrode structure to conduct MnO 2 Electrochemical deposition: the working electrode is the graphene porous fiber obtained in step S3, the counter electrode is a Pt electrode, the reference electrode is a calomel electrode, and the prepared mixed solution of sodium sulfite and manganese sulfate is used as the electrolyte to perform constant current deposition; after the deposition is completed, it is thoroughly washed with deionized water and then dried to obtain a solid supercapacitor fiber electrode.

[0047] Specifically, in the constant current deposition process, the deposition current is 200 to 800 μA·cm -2 , the deposition time is 5 to 30 minutes.

[0048] The concentration of sodium sulfite is 0.5-5 mol / L; the mass ratio of sodium sulfite to manganese sulfate is (5-50):1.

[0049] In a second aspect, the present invention provides a solid-state supercapacitor fiber electrode prepared by the aforementioned preparation method, wherein the prepared solid-state supercapacitor fiber electrode comprises a graphene porous fiber and MnO uniformly loaded on the surface of the graphene porous fiber. 2 The solid-state supercapacitor fiber electrode can provide 516.13mF·cm in the operating voltage range of 0 to 1.2V. -2 Area specific capacity (0.08A·cm -3 At a current density of , the volumetric capacity is 60.49F·cm -3 ).

[0050] Some specific embodiments are listed below. It should be noted that the embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If specific techniques or conditions are not specified in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be obtained commercially.

[0051] Example 1

[0052] This embodiment provides a method for preparing a solid-state supercapacitor fiber electrode, comprising the following steps:

[0053] S1, the concentration of the graphene oxide aqueous solution was 7 mg / ml, 20 ml was measured and ultrasonicated for 2 h, spread on a customized polytetrafluoroethylene mold (100×100×10 mm), and left to stand in a fume hood overnight to obtain a dry graphene oxide film;

[0054] S2, weigh 5.04g of KOH, pour it into 30ml of deionized water, mix it evenly, and obtain a KOH aqueous solution; then, repeatedly spray the KOH aqueous solution on the dried graphene oxide film obtained in S1; then, carefully peel off the film with tweezers, twist the graphene oxide film containing KOH, roll it into fibers, and dry it at 60°C for 24h; wherein the mass ratio of graphene oxide to KOH is 1:12;

[0055] S3, calcining the dried sample in an argon atmosphere in a tube furnace, raising the temperature to 280°C at 2° / min, staying for 30 min, then raising the temperature to 650°C at 5° / min, staying for 30 min, washing three times with deionized water for 20 min, and finally drying at 60°C for 12 h to obtain graphene porous fibers (aRGOF);

[0056] S4, weigh 12.19g of anhydrous sodium sulfite, pour it into 70ml of deionized water and stir evenly, then add 1.06g of anhydrous manganese sulfate, mix and stir continuously; use a three-electrode structure to conduct MnO 2 Electrochemical deposition: The working electrode was aRGOF obtained in step S3, the counter electrode was a Pt electrode (10 × 10 × 0.1 mm), and the reference electrode was a calomel electrode (3M KCl). 400 μA cm was applied within 20 min. -2 of constant current.

[0057] After the deposition is completed, the solid-state supercapacitor fiber electrode is obtained by thoroughly washing with deionized water and then drying.

[0058] Examples 2-6 and Comparative Examples 1-3

[0059] Examples 2-6 and Comparative Examples 1-3 provide a method for preparing a solid supercapacitor fiber electrode, which is different from Example 1 in that the mass ratio of graphene oxide to metal hydroxide in step S2 is changed, the type of metal hydroxide is changed, and the constant current deposition time in step S4 is changed, as shown in the following table. The rest is roughly the same as Example 1 and will not be repeated here.

[0060]

[0061]

[0062] Experiments show that among the samples prepared in Examples 1-6, the electrochemical performance of the sample prepared in Example 1 is the best.

[0063] Figure 1 This is a scanning electron microscope image of the solid-state supercapacitor fiber electrode prepared in Example 1. Figure b is an enlarged view of Figure a. It can be seen from Figure a that MnO 2 Evenly attached to the fiber surface; Figure b shows that the graphene fiber surface is porous and MnO 2 It is needle-shaped, and this morphology increases the number of sites on the material surface where redox reactions can occur, giving the material better capacitance.

[0064] Figure 2 This is a CV curve diagram of the solid-state supercapacitor fiber electrode prepared in Example 1 at a voltage sweep rate of 10 mv / s to 500 mv / s. It can be seen that the shape of the CV curve is close to a rectangle, indicating that the material has good capacitance behavior.

[0065] Figure 3 The constant current charge and discharge test results of the solid supercapacitor fiber electrode prepared in Example 1. It can be seen that at 0.4 mA·cm -2At a current density of 516.13 mF·cm -2 The area specific capacity is high even at a current density of 4 mA cm -2 Under this condition, the electrode material still has 219.71mF·cm -2 The area specific capacity shows excellent electrochemical performance.

[0066] Figure 4 This is the AC impedance test result of the solid-state supercapacitor fiber electrode prepared in Example 1 of the present invention. As can be seen from the curve, the material has a low diffusion resistance, indicating that the material has good conductivity, and the structure of the porous graphene fiber is conducive to the transmission and storage of ions in the material.

[0067] In Comparative Example 1, when GO:KOH=1:20, because the graphene oxide and KOH mixed fiber material is over-activated after high-temperature calcination in step S3, the obtained fiber material is very brittle and has a low yield, and can no longer be used as an electrode for the next deposition step.

[0068] In Comparative Example 2, when GO:KOH=1:2, the fiber obtained after calcination was not sufficiently activated and had basically no porous structure.

[0069] In Comparative Example 3, when the constant current deposition time is 40 min, the MnO 2 Agglomeration occurs, and the energy storage capacity of the electrode is greatly reduced. The reason is: the deposition time is too long, MnO 2 Excessive nucleation growth eventually completely covers the fiber surface and agglomerates.

[0070] In Example 6, KOH is replaced by NaOH, and the obtained fiber material also has a porous structure, and the performance of the two is relatively close.

[0071] Comparative Example 4

[0072] Comparative Example 4 provides a method for preparing a solid-state supercapacitor fiber electrode. Compared with Example 1, the difference is that the high-temperature calcination control mode of step S3 is replaced by: increasing the temperature to 650° at 2° / min and staying for 30 minutes.

[0073] Experiments show that when a one-stage heating method is used, the fiber material obtained after high-temperature calcination is very brittle and has a low yield, and can no longer be used as an electrode for the next step of deposition.

[0074] Comparative Example 5

[0075] Comparative Example 5 provides a method for preparing a solid-state supercapacitor fiber electrode. Compared with Example 1, the difference is that the high-temperature calcination control mode of step S3 is replaced by: increasing the temperature to 1050° at 2° / min and staying for 30 minutes.

[0076] Experiments show that the fiber material obtained after high-temperature calcination is very brittle and has a low yield, and can no longer be used as an electrode for the next step of deposition.

[0077] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.

Claims

1. A method for preparing a solid-state supercapacitor fiber electrode, characterized in that: The following steps are involved: S1, spreading a graphene oxide aqueous solution with a concentration of 1 to 40 mg / ml in a mold, and placing it in a fume hood to obtain a dry graphene oxide film; S2, preparing a metal hydroxide solution, and repeatedly spraying the metal hydroxide solution on the dried graphene oxide film obtained in step S1; then, twisting the graphene oxide film containing the metal hydroxide, rolling it into a fiber, and drying it for standby use; wherein the mass ratio of the graphene oxide to the metal hydroxide is 1:(6-16); S3, subjecting the dried sample obtained in step S2 to high-temperature activation calcination in an argon atmosphere in a tube furnace, then ultrasonically washing it with deionized water, and finally drying it to obtain a graphene porous fiber; S4, preparing a mixed solution of sodium sulfite and manganese sulfate, and using a three-electrode structure to perform electrochemical deposition of MnO2: the working electrode is the graphene porous fiber obtained in step S3, the counter electrode is a Pt electrode, the reference electrode is a calomel electrode, and the prepared mixed solution of sodium sulfite and manganese sulfate is used as an electrolyte to perform constant current deposition; After deposition, the solid-state supercapacitor fiber electrode was obtained by thorough washing with deionized water and drying.

2. The method for preparing a solid-state supercapacitor fiber electrode according to claim 1, characterized in that: In step S4, during the constant current deposition process, the deposition current is 200 to 800 μA·cm -2 , the deposition time is 5 to 30 minutes.

3. The method for preparing a solid-state supercapacitor fiber electrode according to claim 1, characterized in that: In step S3, the temperature of the high temperature activation calcination is controlled as follows: raising the temperature to 200-400°C at 2-20°C / min, keeping the temperature for 10-120min, and then raising the temperature to 300-1000°C at 2-20°C / min and staying for 10-120min.

4. The method for preparing a solid supercapacitor fiber electrode according to claim 3, characterized in that: The heating rate in the second stage is greater than that in the first stage.

5. The method for preparing a solid-state supercapacitor fiber electrode according to claim 1, characterized in that: In step S2, the metal hydroxide solution comprises metal hydroxide: deionized water = (1-20 g): (50-500 mL).

6. The method for preparing a solid-state supercapacitor fiber electrode according to claim 1, characterized in that: The metal hydroxide solution is a sodium hydroxide solution or a potassium hydroxide solution.

7. The method for preparing a solid-state supercapacitor fiber electrode according to claim 1, characterized in that: In step S4, the concentration of the sodium sulfite is 0.5-5 mol / L; the mass ratio of the sodium sulfite to manganese sulfate is (5-50):

1.

8. The method for preparing a solid-state supercapacitor fiber electrode according to claim 1, characterized in that: In step S2, during the drying process, the drying temperature ranges from 20 to 200°C and the drying time ranges from 12 to 48 hours.

9. The method for preparing a solid-state supercapacitor fiber electrode according to claim 1, characterized in that: In step S1, the material of the mold is polytetrafluoroethylene.

10. A solid-state supercapacitor fiber electrode, characterized in that: The method is prepared according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • High-strength, compact and ordered porous graphene fiber and continuous preparation method thereof

    CN103726133A

  • Graphene-doped polyacrylonitrile mesopore activated carbon fiber and preparation method thereof

    CN105544020A

  • Ordered porous high-conductivity graphene fibers as well as preparation method and application thereof

    CN112779632A

  • Vertically-aligned graphene-carbon fiber hybrid electrodes and methods for making same

    US20210147999A1

  • Facile preparation of carbon nanotube hybrid materials by catalyst solutions

    WO2017164963A2